Experiments with plants said to be toxic to cattle in northeastern Brazil, which resulted negative - Canella, Camillo F. C.; Tokarnia, Carlos Hubinger; Döbereiner, Jürgen (Pesquisa Agropecuaria Brasileira, 2024)
Seven plants indigenous to northeastern Brazil which had either been reported in the literature or were held in common belief to be poisonous were fed to cattle and observations made. The following plant species and part of the plant fed were used: Abrus precatorius L., leaves and stems; Caesalpinia bracteosa Tul., pods; Calotropis procera R. Br., leaves and fruits given separately; Piptadenia macrocarpa Bth., leaves and pods given separately; Portulaca oleracea L., aerial parts; Ricinus communis L., leaves; Schultesia guianensis (Aubl.) Malme., aerial parts. The experimental animals suffered no obvious adverse effects to any of the plant material given.